Risk Factors and Outcomes of Acute Myocardial Infarction in a Cohort of Antiphospholipid Syndrome - Gan, Yuzhou; Zhao, Yawei; Li, Gongming; Ye, Hua; Zhou, Yunshan; Hou, Chang; Wang, Lan; Guo, Jianping; Li, Chun (Frontiers in Cardiovascular Medicine, 2022)
Background: Antiphospholipid syndrome (APS) is a disorder associated with thromboembolic disease, including acute myocardial infarction (AMI). Given that AMI is a relatively common condition with poor prognostic features, identification of risk factors for AMI in APS is important. Methods: A retrospective cohort of 332 patients with APS were performed in the Department of Rheumatology, Peking University People’s Hospital, from July 2009 to January 2021. Patients were offered outpatient follow-up for 5 years. Clinical data and laboratory parameters were analyzed to identify risk factors for AMI in APS. Primary clinical outcome was all-cause mortality and second clinical outcome was recurrence of thrombosis. Results: Two hundred and thirty-nine thrombotic APS patients were enrolled. AMI was seen in 12.1% (29/239) APS patients, and patients with AMI had multiorgan thrombosis (55.1% vs. 34.3%, p=0.029), recurrent thrombosis (58.6% vs. 34.3%, p=0.011), higher incidence of atherosclerosis (62.1% vs. 23.8%, p<0.001), higher levels of neutrophil counts (×109/L) (4.68 [3.25, 8.17] vs. 3.71 [2.64, 5.80], p=0.036), longer QT interval (ms) (438ms [423, 454] vs. 425ms [410, 446], p=0.016) and less venous thrombosis events (62.1% vs. 63.3%, p<0.001). With age and sex adjusted, the multivariate logistic models revealed multiorgan thrombosis (OR 8.862, 95%CI: 1.817-43.212, p=0.007), atherosclerosis (OR 5.397, 95%CI: 1.943-14.994, p=0.001) and elevated levels of neutrophil counts (>6.3×109/L) (OR 3.271, 95%CI: 1.268-8.440, p=0.014) were risk factors for AMI, and venous thrombosis (OR 0.106, 95%CI: 0.036-0.314, p<0.001) was a protective factor for AMI. By Kaplan-Meier analysis, recurrence rate of arterial thrombosis differed significantly between APS patients with AMI and without AMI (HR=3.307, p=0.038). Conclusion: In APS, atherosclerosis, multiple thrombosis and elevation of neutrophils might serve as risk factors for AMI, and venous thrombosis might be a protective factor for AMI. The fact that AMI only associated with subsequent recurrence of arterial thrombosis, making it important to differently research on venous and arterial in thrombotic APS.